Method and device for measuring position of new classical tearing mode in real time based on microwave reflection - ZHANG TAO; WU MINGFU; LIU YUKAI; YE KAIXUAN; XIANG HAOMING; ZHONG FUBIN; WEN FEI; ZHOU ZHEN; GENG KANGNING; LI GONGSHUN; GAO XIANG; HUANG JIA; et al. (2021)
The invention relates to a method and device for measuring the position of a new classical tearing mode in real time based on microwave reflection, the device comprises a microwave diagnosis system, a magnetic diagnosis system, a data acquisition system and a real-time calculation system, the real-time calculation system is used for processing signals of the diagnosis system, extracting signal features, identifying and judging the new classical tearing mode, and calculating the position. According to the method and the device, the position of the new classical tearing mode is measured in real time, meanwhile, low-clutter current driving interference is avoided, and cooperative work with a low-clutter current driving system is achieved. 本发明涉及一种基于微波反射实时测量新经典撕裂模位置的方法和装置，该装置包括微波诊断系统，磁诊断系统，数据采集系统和实时计算系统，所述实时计算系统用于对诊断系统的信号进行处理，并提取信号特征，识别判断新经典撕裂模，并计算其所在位置。该方法和装置在实时测量新经典撕裂模位置的同时避免了被低杂波电流驱动干扰，实现了与低杂波电流驱动系统的协同工作。